2022
DOI: 10.3390/antiox11030553
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of the Improvement of Glucose Homeostasis in Type 2 Diabetes by Pomegranate Juice

Abstract: Pomegranate is a polyphenol-rich fruit. Studies have shown that extracts prepared from its juice or from different parts of the pomegranate plant have various biological activities including antioxidant, antimicrobial, anti-inflammatory, anticarcinogenic, cardioprotective, and antidiabetic. The therapeutic potential has been attributed to various phytochemicals, including ellagic acid, punicic acid, flavonoids, anthocyanidins, anthocyanins, flavonols, and flavones. This review focuses on the scientific evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
(77 reference statements)
0
13
0
1
Order By: Relevance
“…Also, it has been shown that the peroxisome proliferator-activated receptor gamma (PPAR-γ) pathway is affected by the punicic acid continent of pomegranate juice which in turn, modulates glucose uptake and diabetes-induced inflammation [ 36 ]. Based on Olvera-Sandoval et al (2022) study, the antidiabetic content found in pomegranates helps reduce blood sugar levels in T2DM patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been shown that the peroxisome proliferator-activated receptor gamma (PPAR-γ) pathway is affected by the punicic acid continent of pomegranate juice which in turn, modulates glucose uptake and diabetes-induced inflammation [ 36 ]. Based on Olvera-Sandoval et al (2022) study, the antidiabetic content found in pomegranates helps reduce blood sugar levels in T2DM patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease was significantly higher in AT+PJI than in AT or PJI alone. Pomegranate juice might decrease the activity of ALT, AST, and GGT enzymes probably by reducing blood glucose, glycation of antioxidant enzymes, and increasing the clearance of ROS [ 37 ]. As pomegranate juice contains many polyphenolic and flavonoid compounds, it has strong antioxidant properties and prevents oxidative stress in the body [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These hydrocarbons in the form of sucrose, starches, and fibers are broken down into glucose, which is subsequently absorbed, causing spikes in the systemic glycemia ( Prasad et al, 2019 ). The cleavage of these macromolecules is under the control of key enzymes involved in carbohydrate digestion, such as α-glucosidase, β-glucosidase, and α-amylase ( Al-Zuhair et al, 2010 ; Ramzi and Hosseininaveh, 2010 ; Olvera-Sandoval et al, 2022 ). Thereby, inhibiting or slowing down the activity of these target enzymes may effectively reduce the postprandial hyperglycemia and, therefore, successfully contribute to the management of diabetes mellitus ( Khatib et al, 2022a ).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…A baixa ingestão de compostos bioativos, que podem ser encontrados em vegetais, está associada ao risco de desenvolvimento de DCNT, assim como o superávit calórico (consumo de mais calorias do que está sendo gasto), e consumo excessivo de gorduras totais e saturadas (FERNANDES et al, 2020). Esses compostos privilegiam o armazenamento de energia, impedindo lipólise e aumentando a captação de glicose, auxiliando na homeostase glicêmica OLVERA-SANDOVAL et al, 2022), também podem auxiliar na modulação de citocinas próinflamatórias na obesidade (OLIVEIRA et al, 2020;MARTINEZ et al, 2022). O consumo de alimentos ricos em compostos bioativos atua no processo inflamatório, que aliado a atividade física, é um ótimo candidato na redução do risco de aparecimento de DCNT (DIREITO et al, 2021).…”
Section: Condições De Riscounclassified